Identification, Isolation and Characterization of IGF Binding Proteins as a Secretable Proteins of Human Endometrial Stromal Cell Culture - Gamal A. M. Singer, Thomas Strowitzki, Jihan Hussein, Fatma Oraby (Journal of Applied Pharmaceutical Science, 2014)
IGF-1, a high potent mitogenic factor with a dual function is believed to participate with female steroids and other growth factors to prepare endometrium receptivity for successful embryo implantation and further development. Stromal cells forms the functional receptive layer of endometrium structure. Analysis of the conditioned/defined medium of pure cultured human endometrial stromal cells have revealed that stromal cells in a monolayer culture secrete and produce three different types of proteins in a varying amounts. These proteins exhibit a high specificity as well as a high binding affinity for the radiolabeled IGF-1 peptide. The molecular weights of these proteins have been determined by SDS-Page electrophoresis after cross-linking with the radiolegand IGF-1 and then detected with autoradiography. By comparison to the migration of high molecular weights protein markers, these proteins have been identified to correspond to the IGFBP-1 (31 KDa), IGFBP-2 (36 KDa) and IGFBP-3 (45 KDa). The secretion of these binding proteins (IGFBP-1, -2, -3) by endometrial stromal cells may support the view of their biological importance in controlling the delivery and bioavailability of the high mitogen IGF-1 peptide to their nominative type-1 IGF-receptor on cell surface, thereby modulating its action. It seems likely that these IGFBPs may play a key role in switching on/off IGF-1 peptide action , thereby avoiding the uncontrolled proliferation effect of the IGF-1 that favor endometrium cancer development.
Keywords: IGFBPs, Cell culture, Endometrial Stromal cells.